2008
DOI: 10.1063/1.2891062
|View full text |Cite
|
Sign up to set email alerts
|

Resonance-enhanced dipolar interaction between terahertz photons and confined acoustic phonons in nanocrystals

Abstract: Articles you may be interested inEffects of nanocrystal shape and size on the temperature sensitivity in Raman thermometry Appl. Phys. Lett. 103, 083107 (2013); 10.1063/1.4819170 Acoustic phonon strain induced mixing of the fine structure levels in colloidal CdSe quantum dots observed by a polarization grating technique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Fundamental modes are thus preferentially observed, yielding access to their characteristics, i.e., frequency and damping. Quite generally, the observed dominant modes are different from those detected in spectrally resolved techniques, i.e., mostly spontaneous Raman spectroscopy [22,23,25,167,224,229], infrared spectroscopy being used only very scarcely in this context [88][89][90]. The time and frequency domain approaches are thus complementary, but the main advantage of the first one is the very large range of accessible particle sizes, from about 1 to 100 nm, with vibrational mode frequencies in the THz to 10 GHz range [39,71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamental modes are thus preferentially observed, yielding access to their characteristics, i.e., frequency and damping. Quite generally, the observed dominant modes are different from those detected in spectrally resolved techniques, i.e., mostly spontaneous Raman spectroscopy [22,23,25,167,224,229], infrared spectroscopy being used only very scarcely in this context [88][89][90]. The time and frequency domain approaches are thus complementary, but the main advantage of the first one is the very large range of accessible particle sizes, from about 1 to 100 nm, with vibrational mode frequencies in the THz to 10 GHz range [39,71].…”
Section: Discussionmentioning
confidence: 99%
“…1) are Raman active, the latter usually exhibiting larger Raman scattering cross-sections and thus dominating the Raman spectra [86,87]. The l = 1 modes are optically active and have been observed in THz absorption experiments [88][89][90]. Because of the isotropy of the excitation process (Section 3), only the isotropic l = 0 modes, associated to purely radial displacement field, ⃗ u(⃗ r) = u(r)⃗ e r (with ⃗ r = r⃗ e r ), are observed in time-resolved experiments ( Fig.…”
Section: Spherical Objectsmentioning
confidence: 96%
“…There have been numerous experimental and theoretical studies on the acoustic vibrations of nanoparticles in the last few decades. These vibrations have been observed by a variety of experimental techniques including lowfrequency Raman scattering, 1 time-resolved femtosecond pump-probe experiments, 2-4 infrared absorption, 5,6 inelastic neutron scattering, 7 and persistent spectral hole burning. 3 Reasonable estimates for the mode frequencies are obtained using the 1882 Lamb solution of the continuum elastic problem for an elastically isotropic homogeneous free sphere.…”
Section: Introductionmentioning
confidence: 99%
“…This resonant microwave absorption process is through the dipolar coupling of electromagnetic waves with the specific “dipolar” vibration modes of the same frequency in the spherical viruses, assisted with the inherent core-shell charge separation of the nano-sphere-like virions 24 . Since it is a resonant conversion of a photon into a phonon of the same energy, this energy transfer is highly efficient and thus provides a new strategy for virus epidemic prevention in open public.…”
Section: Introductionmentioning
confidence: 99%
“…By treating icosahedral viruses as nano-spheres, a recent study has shown highly efficient structure-resonant energy transfer from microwave to the confined acoustic vibration modes of spherical viruses 1 , which results in deactivation of flu viruses with microwave power below the IEEE standard that is safe in open public space. This resonant microwave absorption process is through the dipolar coupling of electromagnetic waves with the specific “dipolar” vibration modes of the same frequency in the spherical viruses, assisted with the inherent core-shell charge separation of the nano-sphere-like virions 2 4 . Since it is a resonant conversion of a photon into a phonon of the same energy, this energy transfer is highly efficient and thus provides a new strategy for virus epidemic prevention in open public.…”
Section: Introductionmentioning
confidence: 99%